Gastrointestinal Tonometry in the Perioperative Period of Liver Transplantation: An Integrative Review - Brito, Tatiany Cíntia da Silva; Xavier, Sabrina Priscila de Souza; Teixeira, Breno Pereira; Silva, Carolline Eronita da; Falcão, Jefferson Aires; Silva, Lívia Farias da; Santana , Artur Guilherme Caldas de; Batista, Pedro Henrique Mafra dos Santos Nogueira; Silva, Hugo Rafael de Souza e; Izidio de Lima, Manuela; Cirilo Lucena da Fonseca Neto, Olival (Brazilian Journal of Transplantation, 2024)
Introduction: Gastric tonometry is a useful tool for examining regional splanchnic perfusion as it provides an indirect assessment of the state of the liver graft. This is because splanchnic hypoperfusion is a critical parameter in the context of liver transplantation, being associated with the development of problems such as acute liver failure and multiple organ failure. Objective: To analyze the effects of gastrointestinal tonometry in the perioperative period of patients undergoing liver transplantation. Methodology: This is an Integrative Review using the PubMed and VHL databases. The following descriptors were used: “Tonometry”, “Splanchnic circulation” and “Liver transplantation” with the Boolean operator “AND”, and articles of relevance to the topic were selected. Initially, 24 articles were selected, all published in the last 20 years, in Portuguese and/or English. After analysis, 6 articles matched the proposed objective. Results: It was observed that the difference between PraCO2 at the end of surgery and in the anepathic phase was greater in patients without liver graft dysfunction. A positive correlation was found between ΔpraCO2 and peak ALT after liver transplantation. In another study, it was found that the relationship between poor graft function was the presence of elevated liver enzymes, worsening synthetic liver function, coagulopathy and encephalopathy. It has also been shown that intramucosal gastric pH can predict early graft function. In a group with liver dysfunction, patients had an intramucosal gastric pH of less than 7.3 in the perioperative period, which remained low until the 24th hour postoperatively, while the group without dysfunction had an intramucosal gastric pH of more than 7.3, except in the anepathic phase when it was below this value. Conclusion: The usefulness of gastrointestinal tonometry to monitor splanchnic circulation and liver graft function during liver transplantation has been described and although support for this statement was found in some studies, this review had limitations due to the small number of articles available, which prevents it from covering a wide range of scientific evidence.